Hubungan Kualitas Pelayanan Terhadap Kepuasan Waktu Tunggu Racikan Obat Poli Anak di Instalasi Farmasi Rawat Jalan RSDH Cianjur: The Relationship of Service Quality to Satisfaction with Waiting Time for Compound Medication Outpatient Children's Poly in RSDH Pharmacy Unit Cianjur - Ajeng Selva Fauziah; Riasa Barata Nian; Julia Totong (UIMA Press, 2024)
Patient satisfaction is an important and commonly used indicator to measure the quality of health services. Patient satisfaction influences the delivery of quality health services that are timely, efficient, and patient-centered. This research was conducted to measure the satisfaction of outpatient pediatric polyclinic patients at the Dr. Hospital Pharmacy Installation. Hafiz Cianjur in 2023 regarding the waiting time for the compounded medicine service provided. A non-experimental research method was used with a cross-sectional design using questionnaire distribution. A total of 91 patients were involved as respondents (research sample). The validity test results show that the calculated r value for all variables is greater than the table r value. Cronbach's Alpha score on the reliability test is more than 0.6. It is stated that the questionnaire (research instrument) is valid and reliable. The correlation coefficient value of service quality and patient satisfaction is 0.656, indicating that there is a strong relationship between service quality and patient satisfaction. The service quality regression coefficient is 0.376; it is stated that every time there is an increase in service quality, patient satisfaction also increases by 37.6%. The Adjusted R2 value is 0.274 or 27.4%. It can be stated that 27.4% of the satisfaction level is the waiting time for dispensing polymedicine for children in the outpatient pharmacy installation at Dr. Hospital. Hafiz Cianjur in 2023 is influenced by the independent variable, namely Service Quality, and 72.6% is influenced by other variables.